An integrative assessment to determine the genotoxic hazard of estuarine sediments: combining cell and whole-organism responses - Costa, Pedro M.; Pinto, Miguel; Vicente, Ana M.; Gonçalves, Cátia; Rodrigo, Ana P.; Louro, Henriqueta; Costa, Maria H.; Caeiro, Sandra; Silva, Maria J. (Frontiers in Genetics, 2014)
The application of the Comet assay in environmental monitoring remains challenging in face of the complexity of environmental stressors, e.g. when dealing with estuarine sediments, that hampers the drawing of cause-effect relationships. Although the in vitro Comet assay may circumvent confounding factors, its application in environmental risk assessment (ERA) still needs validation. As such, the present work aims at integrating genotoxicity and oxidative DNA damage induced by sediment-bound toxicants in HepG2 cells with oxidative stress-related effects observed in three species collected from an impacted estuary. Distinct patterns were observed in cells exposed to crude mixtures of sediment contaminants from the urban/industrial area comparatively to the ones from the rural/riverine area of the estuary, with respect to oxidative DNA damage and oxidative DNA damage. The extracts obtained with the most polar solvent and the crude extracts caused the most significant oxidative DNA damage in HepG2 cells, as measured by the FPG (formamidopyrimidine-DNA glycosylase)-modified Comet assay. This observation suggests that metals and unknown toxicants more hydrophilic than PAHs may be important causative agents, especially in samples from the rural part of the estuary, where oxidative DNA damage was the most significant. Clams, sole and cuttlefish responded differentially to environmental agents triggering oxidative stress, albeit yielding results accordant with the oxidative DNA damage observed in HepG2 cells. Overall, the integration of in vivo biomarker responses and Comet assay data in HepG2 cells yielded a comparable pattern, indicating that the in vitro FPG-modified Comet assay may be an effective and complementary line-of-evidence in ERA even in particularly challenging, natural, scenarios such as estuarine environments.